A Hybrid Course for Probability and Statistics for Engineers: An E-Readiness Study at Shahid Beheshti University - Payandeh, Amir T; Omidi, Maryam (International Journal of Emerging Technologies in Learning (iJET), 2010)
Probability and Statistics for Engineers covers verities of subjects in the set theory, the combinatory analysis, probability, statistics, and (in some universities) the stochastic processes. Since, course receives only 3 credits it has to be thought 3 hours/week. This overloading content along with time limitation make course as a challenging and difficult one for students. Also, many instructors, including the first author, found the course very challenging to teach. Two popular on-site and e-learning training systems do not provide any appropriate solution. This article suggests a hybrid training system, which combines some elements of both training systems to reduce the disadvantages of both systems. Readiness of such hybrid course is measured by preparedness of students for online activities. The readiness study at Shahid Beheshti University shows that Internet skills, self-directed learning, learner attitude toward e-learning, e-mail skills, and software ability of students are factors which are significantly affect readiness of students.